Parental phubbing and academic burnout in adolescents: the role of social anxiety and self-control - Jiang, Yuqian; Lin, Lu; Hu, Ronghua (Frontiers in Psychology, 2023)
In this research, we examined the relationship between parental phubbing and adolescents’ academic burnout, and whether social anxiety and self-control play a mediating role in it. We used 4 questionnaires to investigate parental phubbing, social anxiety, self-control, and the adolescents’ leaning burnout among 882 high school students in Wuhu and Huangshan city, Anhui province, China. The findings indicated that: (1) parental phubbing, social anxiety, and self-control all significantly predict adolescents’ academic burnout directly; (2) parental phubbing could indirectly influence adolescents’ academic burnout through three pathways: the separate mediating effect of social anxiety and self-control, and the chain mediating effect on both. The results of this study help parents understand how their phubbing actions affect adolescents' academic burnout and the mechanism of action.